Post-event Simulation and Analysis of "9.7" Extreme Heavy Rainstorm and Flooding in Shenzhen River Basin - LIU Xunping; ZHENG Jingwei; WANG Zheng; WANG Mengjie (Renmin Zhujiang)
From September 7 to 8, 2023, Shenzhen experienced an extreme heavy rainstorm with historical intensity. Specifically, the Shenzhen River Basin, located at the center of the storm, broke five historical records. The "9.7" extreme heavy rainstorm caused flood levels in the Shenzhen River and the Buji River to exceed historical maximums, leading to widespread flooding across the basin. By collecting and analyzing rainfall data for the Shenzhen River Basin during the "9.7" extreme heavy rainstorm and conducting flood mark surveys, this paper developed an urban flood-waterlogging coupled model covering hydrology, river channels, surface runoff, and drainage. The model was rigorously calibrated by field-measured rainfall, water level, and flood mark data. The simulated and measured water level processes were in good agreement, with the absolute error in the maximum water levels and flood mark depths being within ±0.2 m. Based on flood mark surveys and flood model simulations, the flood risk map for the Shenzhen River Basin during the "9.7" event was reconstructed. The flood risk was mainly concentrated on the downstream of the Buji River and the middle and upper reaches of the Shenzhen River. The flooded area in the Shenzhen River Basin reached 22.62 km², with an area of about 2.88 km² having water depths exceeding 1 m. The flooded area caused by the overflow of the Buji River downstream was about 2.7 km². Through the post-event simulation, weak points and key control areas in flood prevention and management in the Shenzhen River Basin were identified, which provides scientific evidence and decision-making support for subsequent disaster prevention, reduction, and management efforts.